Topsy + Tim Red Boots, Yellow Boots - Adamson, Jean and Adamson, Gareth (Ladybird Books Ltd, 1997)
It's a rainy day, but Tim refuses to wear his wellington boots. More Topsy and Tim fun in this colourful storybook.
Keywords: Action & Adventure; General; Juvenile Fiction